Canggu's Batu Mejan Beach As A Source Of Inspiration For The Creation Of Painting Works - Setiawan, I Made Ricky; Adnyana, I Wayan; Utami, Ni Made Purnami (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2024)
The author discusses the history and atmosphere that the author experienced when creating the work as inspiration for painting. This topic was chosen as a means of conveying to the public what the history and atmosphere of Batu Mejan Beach is like and how the author created it in a work of painting. Creation of works is carried out through the steps of research, creation and presentation of art. This research is qualitative in nature by collecting data through journals related to Batu Mejan Beach. The method used is the Hawkins creation method, namely: idea exploration, improvisation/experimentation and realization. The originality of the work is carried out by the author from the basis of the emergence of an idea to the creation of a work of art using the visual source of coral rocks at Batu Mejan Beach and the addition of objects that have meaning/symbols. The visualization of the work emphasizes the elements of the idea and the techniques in which it is developed, accompanied by a spirit of taste that is built to give an aesthetic impression through the presentation of forms, as well as concepts that are used as references in each work. The result of the creation is a form of visualization of a painting by emphasizing the elements and principles of painting. The creation of this painting work is entitled "Canggu's Batu Mejan Beach as a Source of Inspiration for the Creation of Painting Works" with the output being a final thesis work and six works of painting art. Using palette techniques and acrylic paint materials with an expressionist flow.